TUGAS POKOK DAN FUNGSI (TUPOKSI) APOTEKER DI PUSKESMAS DALAM PELAYANAN OBAT MENURUT PERATURAN PERUNDANG-UNDANGAN - Satvika Devi, Ni Nyoman Adhi (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 10 No 2 (2020): Indonesian Journal of Legal and Forensic SciencesDO - 10.24843/IJLFS.2020.v10.i02.p02, 2020)
Puskesmas is a health service facility that aims to improve public health, which is related to the role of pharmacists in providing good pharmaceutical services. Pharmaceutical services are direct services that are responsible for pharmaceutical preparations in order to achieve quality improvement in patient life. The main duties and functions of pharmacists in health centers include pharmaceutical services regarding drug services and have been regulated in laws and regulations. In practice, it is not yet fully implemented because it is not considered a priority. Various cases of inappropriate drug use have emerged. For this reason, it is necessary to carry out a study on the functions of pharmacists in health centers based on statutory regulations. The method of writing this article is based on literature study through legal rules and regulations which are then linked to cases that occur in society. Various laws have been made by the government to regulate the responsibilities of a pharmacist in carrying out their duties and functions in matters related to pharmaceutical services such as drug services so that they are expected to be able to minimize drug-related cases that occur in the community. The duties and functions of pharmacists which are regulated by law include prescription services, counseling, dispensing, PTO, MESO, and PIO.